FAdail al-Suwar dalam kitab Zubdatu al-Bayan fi Bayani Fadail al-Suwar al-Qur'an karya KH. Shodiq Hamzah Semarang - Mohammad Zamzami Urif (Fak. Ushuluddin dan Pemikiran Islam, UIN Sunan Kalijaga, 2015)
wk, c.1/ws.c.1